Field Study of Lyophilized Calibrant Plasmas for Fresh Plasma INR Determination - van den Besselaar, A. M. H. P.; Houbouyan-Réveillard, L. L. (Thrombosis and Haemostasis, 2002)
An alternative approach to INR estimation is for laboratories to calibrate their own local system using calibrant plasmas supplied by manufacturers or reference laboratories. The purpose of the present study was to investigate the within-laboratory variability of a calibrant plasma procedure using various sets of lyophilized plasmas. INR had been assigned to 13 calibrant plasmas in a previous multi-center study. Each of 10 other (“field”) laboratories measured PTs in the 13 calibrant plasmas and in 15 local fresh coumarin plasmas, using three different thromboplastin reagents. Each fresh coumarin PT was converted to INR using a calibration procedure with a set of 4 calibrants (1 normal + 3 abnormals). The abnormals of each set were either coumarin or artificial and were used with different assigned INR. When the INR had been assigned with a thromboplastin brand identical to the thromboplastin in the field laboratory, the procedure was named “reagent-specific” calibration. Otherwise the procedure was named “dissimilar” calibration. Using “reagent-specific” calibration procedures, relatively homogeneous INR were obtained for the fresh coumarin plasmas, whatever type of calibrant was used. In contrast, discrepant INR were obtained when “dissimilar” cross-species calibration procedures were used. The study was limited to 9 laboratories using the same type of coagulometer and one using a different type.
Keywords: Prothrombin time; INR; thromboplastin; calibrant plasma